Post-Truth and the 'Metropolitan Elite' Feminist: Lessons from Brexit - Cain, Ruth (feminists@law, 2016)
This short comment reflects on gender, age and class profile of those who voted to leave the European Union in the UK's 'Brexit' referendum, and the implications for academic feminists in finding themselves members of a minority holding very different views from and despised by many of those whose interests they have purported to represent.